2022
DOI: 10.1155/2022/1803544
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Single-Cell Transcriptome Analyses Revealed That the Pyroptosis of Glioma-Associated Macrophages Participates in Tumor Progression and Immunosuppression

Abstract: Glioma is the most common of all central nervous system (CNS) malignancies and is associated with a poor prognosis. Pyroptosis has been proven to be associated with the progression of multiple tumors and CNS diseases. However, the relationships between pyroptosis and clinical prognosis and immune cell infiltration are unclear in glioma. In this study, we conducted a comprehensive exploration of pyroptosis in glioma. First, prognosis-related genes were screened at each key regulatory locus in the pyroptosis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Some studies demonstrate that either cancer cells or tumor-derived molecules can act as DAMPs causing inflammasome activation and pyroptosis in macrophages ( 211 , 212 , 214 , 215 , 225 ). Interestingly, it was also reported that pyroptosis and/or inflammasome activation in TAMs can arise as a side effect of various anticancer therapies ( 214 , 215 , 225 , 226 ) or may be triggered by factors other than DAMPs ( 216 , 227 ). In this section, we take a closer look at all this evidence.…”
Section: Tumor Microenvironment: Pyroptosis Necroptosis and Ferroptos...mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies demonstrate that either cancer cells or tumor-derived molecules can act as DAMPs causing inflammasome activation and pyroptosis in macrophages ( 211 , 212 , 214 , 215 , 225 ). Interestingly, it was also reported that pyroptosis and/or inflammasome activation in TAMs can arise as a side effect of various anticancer therapies ( 214 , 215 , 225 , 226 ) or may be triggered by factors other than DAMPs ( 216 , 227 ). In this section, we take a closer look at all this evidence.…”
Section: Tumor Microenvironment: Pyroptosis Necroptosis and Ferroptos...mentioning
confidence: 99%
“…Since macrophage pyroptosis can be induced by a range of factors, DAMPs may not be the exclusive initiators of this process in TME. A recent study on the correlation between the occurrence of TAMs pyroptosis and cancer progression utilizing single-cell RNA-sequencing analysis demonstrated that human glioma-infiltrating macrophages, MDMs in particular, had significant co-expression of caspase-1 and GSDMD genes ( 216 ). Moreover, MDMs from high-grade gliomas showed increased transcripts of pyroptotic genes and their elevated infiltration was a characteristic of the high-risk group.…”
Section: Tumor Microenvironment: Pyroptosis Necroptosis and Ferroptos...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis induced by GSDMD and NLRC4 in high-grade gliomas can promote the progression of gliomas and enhance the sensitivity of these tumors to immune checkpoint therapy by recruiting immune cells ( 127 ). The inflammatory immune microenvironment induced by pyroptosis can promote the invasion and proliferation of glioma stem cells and is also related to the infiltration of M2 pheno-type bone marrow-derived macrophages (BMDMs) ( 72 , 128 ). In the future, it is necessary to construct a GSDMD-deficient mouse model to probe the effects of pyroptosis as a drug target on gliogenesis and the tumor immune microenvironment ( 72 , 127 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%